Light distribution in scattered-trees open woodlands in Western Spain (Agroforestry Systems, 2008)
We have studied the percentage of radiation transmitted through the tree canopy to the underlying pasture and crops in dehesas of Southwest Spain by means of ﬁsh-eye photographs taken at different distances from the tree. Thirty-six trees were studied covering all the diametric classes (0.1–14 m canopy width) of two stands, with mean density of 19 mature trees ha -1 . Intercepted light decreased with distance following an logistic curve, indicating a rapid increase in the light availability with distance from the tree. For mature trees, radiation was constant beyond 20 m. Applying a multivariable regression light equation, distance, stem diameter and canopy width explained more than 88% of the light variability for each orientation studied. A simple model was built up from light equations, tree growth curves and allometric relationships. From this model, we have estimated that radiation available for crops and pasture decreased up to 21% due to the presence of trees in a standard dehesa with 24 mature trees ha -1 and 13% of canopy cover. In addition, we have generated different radiation maps of virtual dehesas differing in tree age, density and arrangement, which could be useful to determine optimal tree planting schemes and consequent pruning and thinning regimes.

Light distribution in scattered-trees open woodlands in Western Spain - Montero, María Jesús; Moreno, Gerardo; Bertomeu, Manuel (Agroforestry Systems, 2008)
We have studied the percentage of radiation transmitted through the tree canopy to the underlying pasture and crops in dehesas of Southwest Spain by means of ﬁsh-eye photographs taken at different distances from the tree. Thirty-six trees were studied covering all the diametric classes (0.1–14 m canopy width) of two stands, with mean density of 19 mature trees ha -1 . Intercepted light decreased with distance following an logistic curve, indicating a rapid increase in the light availability with distance from the tree. For mature trees, radiation was constant beyond 20 m. Applying a multivariable regression light equation, distance, stem diameter and canopy width explained more than 88% of the light variability for each orientation studied. A simple model was built up from light equations, tree growth curves and allometric relationships. From this model, we have estimated that radiation available for crops and pasture decreased up to 21% due to the presence of trees in a standard dehesa with 24 mature trees ha -1 and 13% of canopy cover. In addition, we have generated different radiation maps of virtual dehesas differing in tree age, density and arrangement, which could be useful to determine optimal tree planting schemes and consequent pruning and thinning regimes.
Keywords: allometric relationships; Dehesa; fish-eye photograph; light transmittance; Quercus ilex; radiation map